Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pengunjung pada Event Deliland Festival 2023 - Sela Bertina Vera Elmi Damanik; Sarah Rouli Tambunan (JURNAL RISET MANAJEMEN (JURMA), 2024)
The increase in the number of music festival events in the city of Medan is a phenomenon in this study. To provide satisfaction to visitors, there are several factors, one of which is the quality of service and facilities. The purpose of this study was to determine the effect of Service Quality and Facilities on Visitor Satisfaction at the 2023 Deliland Festival event. The population of this study totaled 19,694 visitors, and the sample used was 100 respondents (slovin). The data used in this research comes from field studies and literature studies in the form of primary and secondary data. This study uses quantitative research methods with descriptive research types which include validity test, reliability test, classic assumption test, hypothesis testing (t test, F test, and analysis coefficient of determination test (R2). The results of the test of the coefficient of determination (R2) show that the variable Quality of Service and Facilities affects Visitor Satisfaction by 74.8% and the remaining 25.2% are influenced by other variables not examined in this study.